Improving dielectric properties of composites thin films with polylactic acid and PZT microparticles induced by interfacial polarization - Bouiri, El Mahdi; Farhan, Rida; Chakhchaoui, Nabil; Oumghar, Khadija; Denktas, Cenk; Eddiai, Adil; Meddad, Mounir; Mazroui, M'Hammed; Cherkaoui, Omar; Omari, Lhaj El Hachemi (EDP SCIENCES S A, 2022)
Although polylactic acid (PLA) is widely identified as a biodegradable polymer, its use is limited due to the inherently poor mechanical properties. Therefore, the strengthening of PLA with microscale particles like lead zirconate titanate (PZT) is a promising field of research that has only just begun to be explored. Piezoelectric polymer-PZT films are encouraging materials for modern technological applications in energy harvesting. The PLA/PZT composites were developed using the solvent casting technique. The mechanical characteristics and dielectric properties of the considered films were investigated. X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Spectroscopy and Scanning Electron Microscopy (SEM) were used, respectively, to examine the influence of these fillers at the molecular level, crystal structure change and micro charges dispersion inside the polymer matrix. Thermogravimetric Analysis (TGA) was used to examine the stability and thermal degradation of the films. The effect of the content (0.1-1 wt.%) of PZT on these properties has also been studied. The results indicate that the addition of PZT content induces considerable improvement in the beta-phase and dielectric constant of microcomposites films compared to that of pure PLA.
Keywords: CRYSTALLIZATION BEHAVIOR; MECHANICAL-PROPERTIES; THERMAL-PROPERTIES; PIEZOELECTRICITY; NANOCOMPOSITES; STEREOCOMPLEX; ENHANCEMENT; GRAPHENE; BLENDS; Physics